Impacts of platelet‐rich fibrin and platelet‐rich plasma on primary osteoblast adhesion onto titanium implants in a bisphosphonate in vitro model. (27th August 2019) - Steller, Daniel; Herbst, Nele; Pries, Ralph; Juhl, David; Klinger, Matthias; Hakim, Samer G.
Abstract: Background: Osteoblast adhesion is a crucial step in osseointegration of dental implants and can be influenced by modification of implant surface or the addition of bioactive agents. Bisphosphonates affect bone turnover, attenuating bone healing in implants patients. PRP and PRF are sources of growth factors involved in osteoblast adhesion, improving subsequent bone healing. The aim of the study was to investigate the impacts of PRP and PRF on adhesion of bisphosphonate‐pretreated osteoblasts on titanium implant surfaces using the cell‐count wash assay, the MTT‐assay as well as real‐time‐cell analyser assay and scanning electronic microscopy. Methods: Titanium implants were colonised for 24 hours with osteoblasts and zolendronic acid, PRP or PRF in different combinations. Afterwards, primary osteoblast adhesion was evaluated by counting the number of attached cells using a wash‐assay cell analysis. Scanning electronic microscopy was performed and evaluated semi‐quantitatively to assess the influence of the different groups on the ultrastructural cell morphology, such as cell size and shape as well as length and number of filopodia. Results: Zoledronic acid led to a decrease of osteoblast adherence onto implant surface. This effect was reversed by adding PRP or PRF. Scanning electronic microscopy showed that both PRP and PRF increased number and length of filopodia in adherent osteoblasts. Conclusions: Zoledronic acid decreased osteoblast adhesion on implant surfaces, and PRF as well as PRP increased primary adhesion of zoledronic acid‐treated osteoblasts on implant surfaces in vitro. Therefore, PRP and PRF may improve initial bone apposition and primary healing of dental implants in patients with bisphosphonate treatment.